Impact of COVID-19 pandemic on birth outcomes: A retrospective cohort study in Nanjing, China - Juan Wen (Frontiers Media S.A., 2022)
IntroductionThe coronavirus disease 2019 (COVID-19) pandemic have significantly affected health care systems and daily wellbeing. However, the indirect impacts of the pandemic on birth outcomes are not fully understood. We aimed to examine whether the pandemic altered risk of adverse birth outcomes.MethodsThis retrospective cohort study included all singleton births during 2016-2020 identified in Women's Hospital of Nanjing Medical University. We compared birth outcomes during COVID-19 pandemic (January-December 2020) with before the pandemic (January-December 2016-2019) using Logstic regression adjusted for confounders.ResultsA total of 19,792 and 92,750 births occurred during and before the pandemic, respectively. Maternal characteristics were similar between groups, except maternal age was higher in pandemic cohort. We observed a reduction in preterm birth (PTB, <37 weeks) during the pandemic [5.9 vs. 5.1%, OR (95%CI) = 0.86 (0.80, 0.92)], but the difference disappeared after multivariable adjustment [adjusted OR (95%CI) = 1.02 (0.94, 1.11)]. Moreover, full term infants born during the pandemic had lower birth weights than those born before the pandemic [adjusted β (95% CI) = −17.4 (−23.9, −10.8)]. Consistently, the risks of low birthweight (LBW, <2,500 g) and small for gestational age (SGA, < P10) were increased [LBW: adjusted OR (95%CI) = 1.13 (1.02, 1.24); SGA: adjusted OR (95%CI) = 1.11 (1.02, 1.21)], and the risks of macrosomia (≥4,000 g) and large for gestational age (LGA, ≥P90) were decreased in the pandemic cohort [macrosomia: adjusted OR (95%CI) = 0.82 (0.77, 0.88); LGA: adjusted OR (95%CI) = 0.73 (0.69, 0.77)].ConclusionIn this study, we observed no change in preterm birth and a decrease in birth weight of full term infants during the pandemic in Nanjing, China.